2016
DOI: 10.1002/2015tc003897
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic intracontinental deformation and exhumation at the northwestern tip of the India-Asia collision-southwestern Tian Shan, Tajikistan, and Kyrgyzstan

Abstract: Along the Ghissar-Alai Range of the southwestern Tian Shan (southwestern Kyrgyzstan, northern Tajikistan), the deformation front of the India-Asia collision-the Pamir-Tibet orogen-is interacting with the intracontinental Tian Shan orogen without the intervening Tarim Craton. Apatite fission track (n = 33,~3.3-145.6 Ma, 27% <10 Ma) and (U-Th)/He (n = 32,~1.9-26.1 Ma, 56% <10 Ma) thermochronologic ages suggest approximate isothermal holding (very slow cooling to weak reheating) during relative tectonic quiescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 113 publications
9
78
0
3
Order By: Relevance
“…Hence, our data support Kässner et al. (); Kässner et al () who suggested a widespread thermal response to late Permian orogensis within the Pamirs and STS.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Hence, our data support Kässner et al. (); Kässner et al () who suggested a widespread thermal response to late Permian orogensis within the Pamirs and STS.…”
Section: Discussionsupporting
confidence: 91%
“…The AFT data obtained in this study record two cooling events that initiated at ~25 Ma and ~10 Ma. The ~25 Ma age corresponds to abundant Oligocene–Miocene AFT ages for major faults within the STS, including in the nearby Ghissar and Garm regions (Figure , Sobel et al., ; De Grave et al., ; Glorie et al., ; Kässner et al, : Bande, Sobel, Mikolaichuk, Schmidt, & Stockli, ). We therefore interpret the ~25 Ma cooling signal to be related to deformation focused along the Vakhsh‐Surkhob fault zone.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations